2016
DOI: 10.1001/jamapsychiatry.2016.2575
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Changes in Gene Expression in Schizophrenia Human-Induced Pluripotent Stem Cell Neurons

Abstract: IMPORTANCE Schizophrenia candidate genes participate in common molecular pathways that are regulated by activity-dependent changes in neurons. One important next step is to further our understanding on the role of activity-dependent changes of genes expression in the etiopathogenesis of schizophrenia. OBJECTIVE To examine whether neuronal activity-dependent changes of gene expression is dysregulated in schizophrenia. DESIGN, SETTING, AND PARTICIPANTS Neurons differentiated from human induced pluripotent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…596 genes were differentially expressed in neurons derived from schizophrenic patients versus controls, reflecting the phenotypic differences between the differentiated neuronal populations (Brennand et al, 2011). Previous work has shown that schizophrenia hiPSC-derived NPCs have aberrant migration (Brennand et al, 2014b) and cellular polarity (Yoon et al, 2014), perturbed WNT signaling (Srikanth et al, 2015; Topol et al, 2015b), increased oxidative stress (Brennand et al, 2014b; Paulsen et al, 2011; Robicsek et al, 2013) and altered responses to environmental stressors (Hashimoto-Torii et al, 2014); while schizophrenia hiPSC-derived neurons exhibit decreased neurite number (Brennand et al, 2011), reduced synaptic maturation (Brennand et al, 2011; Robicsek et al, 2013; Wen et al, 2014; Yu et al, 2014) and synaptic activity (Wen et al, 2014; Yu et al, 2014), and blunted activity-dependent response (Roussos et al, 2016). Extensive immunocytochemical validation of the NPC lines used in the present study showed they are positive for diverse NPC markers including nestin, Sox2, vimentin, Pax6 and TBR2(Brennand et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…596 genes were differentially expressed in neurons derived from schizophrenic patients versus controls, reflecting the phenotypic differences between the differentiated neuronal populations (Brennand et al, 2011). Previous work has shown that schizophrenia hiPSC-derived NPCs have aberrant migration (Brennand et al, 2014b) and cellular polarity (Yoon et al, 2014), perturbed WNT signaling (Srikanth et al, 2015; Topol et al, 2015b), increased oxidative stress (Brennand et al, 2014b; Paulsen et al, 2011; Robicsek et al, 2013) and altered responses to environmental stressors (Hashimoto-Torii et al, 2014); while schizophrenia hiPSC-derived neurons exhibit decreased neurite number (Brennand et al, 2011), reduced synaptic maturation (Brennand et al, 2011; Robicsek et al, 2013; Wen et al, 2014; Yu et al, 2014) and synaptic activity (Wen et al, 2014; Yu et al, 2014), and blunted activity-dependent response (Roussos et al, 2016). Extensive immunocytochemical validation of the NPC lines used in the present study showed they are positive for diverse NPC markers including nestin, Sox2, vimentin, Pax6 and TBR2(Brennand et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In light of the retained spontaneous activity in SCZ iPSC-neurons, Roussos et al [ 76 ] moved on to investigate differences in activity dependent gene expression. Potassium chloride treatment was used for neuronal depolarization of iPSC-derived case/control forebrain neurons.…”
Section: Introductionmentioning
confidence: 99%
“…WGCNA ( 13 , 64 ) uses gene-gene Pearson’s correlation indices as a continuous, i.e., weighted, measure of gene-gene relationships. We computed unsigned networks, i.e., negatively correlated genes are considered connected rather than non-connected ( 65 ). The correlation matrix was transformed into an adjacency matrix by raising Pearson’s coefficients to a positive exponent, β, which is chosen to meet the “scale-free” power law connectivity distribution.…”
Section: Methodsmentioning
confidence: 99%